Six new cases of CRB2‐related syndrome and a review of clinical findings in 28 reported patients. Issue 1 (21st September 2022) - Adutwum, Michelle; Hurst, Anna; Mirzaa, Ghayda; Kushner, Jessica D.; Rogers, Caleb; Khalek, Nahla; Cristancho, Ana G.; Burrill, Natalie; Seifert, Michael E.; Scarano, Maria I.; Schnur, Rhonda E.; Slavotinek, Anne
Abstract: The Crumbs homolog‐2 (CRB2)‐related syndrome (CRBS‐RS) is a rarely encountered condition initially described as a triad comprising ventriculomegaly, Finnish nephrosis, and elevated alpha‐fetoprotein levels in maternal serum and amniotic fluid. CRB2‐related syndrome is caused by biallelic, pathogenic variants in the CRB2 gene. Recent reports of CRB2‐RS have highlighted renal disease with persistent proteinuria and steroid‐resistant nephrotic syndrome (SRNS). We report six new and review 28 reported patients with pathogenic variants in CRB2 . We compare clinical features and variant information in CRB2 in patients with CRB2‐RS and in those with isolated renal disease. The kidneys were the most frequently involved body system and 11 patients had only renal manifestations with SRNS or nephrotic syndrome. Central nervous system involvement was the next most common manifestation, followed by cardiac findings that included Scimitar syndrome. There was a significant clustering of pathogenic variants for CRB2‐RS in exons 8 and 10, whereas pathogenic variants in exons 12 and 13 were associated with isolated renal disease. Further information is needed to determine optimal management but monitoring for renal and ocular complications should be considered. Abstract : We studied 34 patients with Crumbs homolog‐2 related syndrome (CRB2‐RS) and found that the kidneys, brain and heart were most affected. Pathogenic variants in CRB2 clustered in exons 8 and 10 for CRB2‐RS and in 12 and 13 for isolated renal disease.